Experimentação no ensino de química: uma análise dos artigos publicados em revistas da área - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The experimentation is considered a pedagogical tool in the Chemistry teaching, as it can facilitate the understanding of the contents and awaken the curiosity, it contribute to the students’ learning. This research aims to assess the works published in journals of chemistry education, focusing on the use of experimental activities, seeking answers to the question: “experimental activities, proposals in articles published in the chemistry teaching field magazines, contribute to the cognitive development of the students?” For that based on the theory of Vygotsky to clarify if the use of this educational resource in the chemistry teaching contributes to scholar learning. The methodology used for the exploitation of the data is qualitative type, it prioritizing the documentary analysis. For it was listed five magazines for analysis evaluated with Qualis A1, A2 and B1 in the education area. The articles search period extended from 1995 to 2015 and the selection took place through the location of the following expressions: experimentation, trials, experiment(s), experience(s) and experimental activities in the summary, title or the publications keywords. Data analysis occurred through the categorization of articles in: location, level of education, experimental activity situation, interaction between the subjects, experimental activity type, materials used and objectives included in the trial. It was noticed that the activities contained in articles are in accordance with the schools conditions, because approximately 50% of them use alternative materials, which makes reproduction by professor. Also noted that the objectives referred to in most of the trials were: assist students in the development of the ability of observation and analysis of data. In addition, the theory of Vygotsky as theoretical support in relation to the social interactivity. From this analysis, this study regarding the proposals for experimental activities that create opportunities that motivate students to exhibit their ideas, comparing them with the explanation given by professor, as well as moments of interaction between the subject. Identified that 59% of the experiments described by articles do not favor the interaction among students and between these and the professor. Most of the trials (31%) is the demonstrative type, while the investigative and verification activities totaled 26% each. Demonstration activities may not favour the interaction among the subjects, since it is performed by professor while students only observe the experiment. This kind of activity might not contribute as effectively in learning of students, since it does not favor the exchange of knowledge and information among them. However, investigative or verification activities provide moments of interaction, in which students have the opportunity to perform the experiment in groups. Thus, it is concluded that the professor is agent able to establish situations involving the student in the process of teaching and learning. In this context, experimental activities emerge as an interesting alternative didactics to promote learning through Chemistry concepts application and the classroom interaction.
Keywords: Ensino de química; Experimentação; Interação social; Chemistry education; Experimentation; Social interaction; CNPQ::CIENCIAS EXATAS E DA TERRA